Profitabilitas, Investasi Dan Arus Kas Sebagai Prediktor Tingkat Pengembalian Saham - Rowland Bismark Fernando Pasaribu (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2012)
AbstractThis research aim to calculate influence from some financial performance (B/M ratio, market capitalization, earning position, investment, accrual value, company strength measurement, dividend policy, and profitability) to stock return. Multiregression model follow Fama and French procedure. Result of first hypothesis confirmed statistically, that the difference of stock of return pursuant to finance performance not automatically own significant influence in stock return prediction itself. Other result confirmed that all the predictor used has no significant influence to stock return both simultaneously and partial.Keyword: Profitability, Investment, Cashflow, Accrual value, Stock return